Less cash, less theft? Evidence from fintech development in the People's Republic of China - Hongze Jiang; Pinghan Liang (Asian Development Bank Institute (ADBI), 2021)
This research investigates the impact of Fintech development on an important type of crime: theft. Based on Becker's rational criminal theory, we suggest that Fintech development could mitigate theft activities by increasing the earnings from legitimate work, relaxing potential criminals' financial constraints, and reducing the expected gains from theft. We established a unique dataset containing information on more than 1 million theft defendants during the period 2014-18, which we extracted from 874,000 judgment statements. Then, we aggregated them to construct a city-year panel of theft activities and matched it with the city-level economic activities and Fintech development level. The results show that a 1 standard deviation increase in the Fintech development level has a significant association with a 0.39 standard deviation decrease in thefts' density. Robustness checks and instrumental variable estimation support the main results. Further, the development of Fintech reduces thefts' density by reducing residents' cash holding and providing more job opportunities. Finally, we utilized a nationally representative household survey to estimate the cost of theft for households, finding that victims suffer from more mental health problems, increasing their health expenditure. Our results suggest an unexpected source of welfare gain from the development of Fintech: an improvement in public security.
Keywords: G59; K14; K42; C81; 330; fintech; theft; crime; People's Republic of China